Legal Interest: the Problems of Notion and Correlation with Legal Right and Legal Duty - Tatiana A. Solodovnichenko (Сибирское юридическое обозрение, 2016)
The article contains the notion of legal interest. The author analyzes the problems of distinguishing legal interest from the subjective legal right and legal duty.